Educational belwilderment - Herrera Cuesta, Damián (Nómadas. Critical Journal of Social and Juridical Science, 2011)
After de failure of educacional pact 2010, we ask ourselves about the differences between educational policies of the most important politics parties in Spain: P.P. (Patido Popular) u P.S.O.E. (Partido Socialista Obrero Español). Specially we interested about the educational proposals of P.P. (Partido Popular). In the analysis emphasize the repetition of two main proposals for action and practise of educational policies of the right-wing Spanish. These proposals are ownership and freedon of choice of school. Thinking in the theoretical justifications of a political exponent and important reference of P.P. about educational policy, Francisco López Rupérez –current president of Community School Board of Madrid-, we propose an exercise of exploration of future possibilities, comparing the results expected by the author after the implementation of state subsidy of private school with indications that the practice has left to is to date. So that we analyze the study of Dr. Ana Villarroya Planas (it was made in 2000), about the effects of application of state subsidy of private school in Spain.
Keywords: school; education policy; freedom of choice of school; fexibility; key competences